Analysis of Physical and Chemical Parameters in the Raw Water Processing at Perumda Tirtanadi Sunggal - Sabila, Widya; Nanda, Meutia; Purba, Faiqah Adnin; Rizqi, Puan Maulida Syifa; Harahap, Rosida Sapriani; Listiani, Lia; Dewi, Sentia (PROMOTOR, 2025)
Raw water sources are essential in providing clean water, and their quality must be maintained to meet health standards. The quality of raw water is affected by environmental conditions, rainfall, and human activities along river flows. Domestic, agricultural, and industrial activities often lead to pollution through suspended particles, chemical compounds, and organic materials that increase turbidity and alter the water’s physical and chemical properties. Therefore, effective treatment is needed to ensure water is safe for consumption. This study aims to analyze the physical and chemical parameters in the raw water treatment system at Perumda Tirtanadi Sunggal. The research used a qualitative descriptive method through field observations and secondary data from laboratory tests conducted at the same location. The physical parameters observed were temperature, color, and turbidity, while the chemical parameters included pH, ammonia, nitrate, nitrite, organic substances, and metal contents such as Fe, Mn, and Al. The raw water originated from the middle part of Sei Belawan, an area susceptible to pollution from domestic, agricultural, and industrial waste. Results showed that the turbidity and Fe content of the raw water exceeded raw water testing standards. However, after treatment, all parameters met the Indonesian drinking water quality standards as stated in the Minister of Health Regulation No. 2 of 2023 and Government Regulation No. 22 of 2021 concerning Environmental Protection and Management. The study emphasizes that continuous improvement of the treatment process is essential to maintain high water quality throughout the distribution system in accordance with hygiene and sanitation standards.